The complete mitochondrion genome of the Hoge’s Side-necked turtle Ranacephala hogei (Chelidae), a critically endangered species from South America - Ana Teresa Dumans; Alexandre Pedro Selvatti; Deise Schroder Sarzi; Carolina Furtado; Gláucia Drummond; Marcos Coutinho; Daniel Cardoso Carvalho; Francisco Prosdocimi (Genetics and Molecular Biology)
Abstract The Hogei’s side-necked turtle, Ranacephala hogei, an endemic species of the Southern Paraíba basin, is the most endangered species of chelonians in Brazil. Here, we sequenced, assembled and described the complete mitogenome for R. hogei. The circularized mitogenome of R. hogei was 16,513 bp in length, containing all the typical 13 protein-coding genes, 2 rRNAs, 22 tRNAs and the D-loop region, as expected for animal mitogenomes. The gene arrangement also met the expectation for vertebrates, though R. hogei NAD6 gene was shorter than observed in other closely related species. Additionally, we provided an assembly of the Podocnemis expansa mitochondrial genome based on public data in SRA database. Maximum likelihood and Bayesian phylogenomic trees were constructed using the concatenation of the alignments of all protein coding and ribosomal genes and compared to the data obtained from other 15 complete mitochondrial genomes available for the suborder Pleurodira plus five Cryptodira taxa as outgroups in the GenBank database. Our phylogenomic results placed the mitogenome of R. hogei in a monophyletic South American clade which is deeply within the family Chelidae, corroborating the evolutionary affinities of the sequence. The remaining phylogenomic results also agrees with previous phylogenetic studies in Pleurodira, namely the reciprocal monophyly of the Australasian and South American Chelidae clades, and the monophyly of all higher clades such as families and suborder.